The war on terror and the laws of war : a military perspective - Corn, Geoffrey S. (Oxford ; New York, NY : Oxford University Press, 2015)
Many years after the United States initiated a military response to the terrorist attacks of September 11, 2001, the nation continues to prosecute an armed conflict against transnational terrorist groups. Today, it remains just as vital to understand how the law of armed conflict applies to and regulates military operations executed within the scope of this armed conflict against transnational non-state terrorist groups. In The War on Terror and the Laws of War, seven legal scholars, each with experience as military officers, focus on how to strike an effective balance between the necessity of using armed violence to subdue a threat to the nation with the humanitarian interest of mitigating the suffering inevitably associated with that use. Each chapter addresses a specific operational issue, including the national right of self-defense, military targeting and the use of drones, detention, interrogation, and trial by military commission of captured terrorist operatives, while illustrating how the law of armed conflict influences resolution of that issue. This Second Edition carries on the critical mission of continuing the ongoing dialogue about the law from an unabashedly military perspective, bringing practical wisdom to the contentious topic of applying international law to the battlefield. Book jacket.
Introduction / Geoffrey S. Corn -- Legal basis for the use of armed force / Geoffrey S. Corn -- Triggering the law of armed conflict? / Geoffrey S. Corn -- Targeting of persons and property / Eric T. Jensen -- Interrogation and treatment of detainees in the global war on terror / Dick Jackson -- Detention of combatants and the war on terror / James A. Schoettler, Jr. -- Trial and punishment for battlefield misconduct / Dru Brenner-Beck -- Battlefield perspectives on the laws of war / Michael W. Lewis.
Includes bibliographical references and index.
Keywords: 2001-2009; War on Terrorism, 2001-2009.; Terrorism -- Prevention -- Law and legislation; War (International law); Terrorism -- Prevention -- Law and legislation; War; Terrorism